Seeking progress in disease modification in Parkinson disease. (September 2021) - Lungu, Codrin; Cedarbaum, Jesse M.; Dawson, Ted M.; Dorsey, E. Ray; Faraco, Carlos; Federoff, Howard J.; Fiske, Brian; Fox, Robert; Goldfine, Andrew M.; Kieburtz, Karl; Macklin, Eric A.; Matthews, Helen; et al.
Abstract: Objective: Disease modification in Parkinson disease (PD) has remained an elusive goal, in spite of large investments over several decades. Following a large meeting of experts, this review article discusses the state of the science, possible reasons for past PD trials' failures to demonstrate disease-modifying benefit, and potential solutions. Methods: The National Institute of Neurological Disorders and Stroke (NINDS) convened a meeting including leaders in the field and representatives of key stakeholder groups to discuss drug therapy with the goal of disease modification in PD. Results: Important lessons can be learned from previous attempts, as well as from other fields. The selection process for therapeutic targets and agents differs among various organizations committed to therapeutic development. The areas identified as critical to target in future research include the development of relevant biomarkers, refinements of the targeted patient populations, considerations of novel trial designs, and improving collaborations between all stakeholders. Conclusions: We identify potential barriers to progress in disease modification for Parkinson's and propose a set of research priorities that may improve the likelihood of success. Highlights: A long history of attempting disease modification in Parkinson's disease has failed to yield successful therapies. Key areas of focus include population selection for trials, markers of therapeutic target engagement, and biomarker development. Harmonizing prospective research efforts among stakeholders is likely to yield increased efficiencies.